1992
DOI: 10.1111/j.1365-2796.1992.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of regional body fat distribution: comparison between W/H ratio and computed tomography in obese women

Abstract: Measurements of regional body fat distribution as determined by waist-to-hip ratio and visceral-to-subcutaneous adipose tissue ratio were compared in 63 obese women. Subjects were divided into three CT-evaluated tertiles on the basis of visceral-to-subcutaneous adipose tissue ratio (group I, 0.05-0.231; group II, 0.232-0.344; group III, 0.345-0.781). The three groups showed no appreciable differences in body weight, body mass index or total abdominal adipose tissue. Waist-to-hip ratio values were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 12 publications
3
11
0
1
Order By: Relevance
“…Healthy women with high VAT had significantly higher concentrations of TG and ApoB and non-significant higher levels of TC and LDL-C, when compared to healthy women with low VAT. This is similar to what has been noted in men 23 and in premenopausal women, 24 but different from older 10 or more obese postmenopausal women with high VAT 25 in whom TC and LDL-C have been significantly higher. However, TC and LDL-C had significant univariate and multivariate correlation with VAT in our healthy women, which persisted after adjusting for confounding variables.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Healthy women with high VAT had significantly higher concentrations of TG and ApoB and non-significant higher levels of TC and LDL-C, when compared to healthy women with low VAT. This is similar to what has been noted in men 23 and in premenopausal women, 24 but different from older 10 or more obese postmenopausal women with high VAT 25 in whom TC and LDL-C have been significantly higher. However, TC and LDL-C had significant univariate and multivariate correlation with VAT in our healthy women, which persisted after adjusting for confounding variables.…”
Section: Discussionsupporting
confidence: 76%
“…As has been reported in men 23 and in premenopausal women, 25 in the present study, healthy women with high VAT had significantly higher fasting insulin and glucose levels, suggesting insulin resistance. 27 This finding is in agreement with a recent study by Brochu et al, 8 where by using hyperinsulinemic=euglucemic clamp technique it was demonstrated that VAT is an important and independent predictor of glucose disposal in apparently healthy postmenopausal women.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, our measurement sites differed from those of previous studies. 6,17,18 Instead of skin landmarks, we used bone landmarks, the midway between the lower rib margin and the superior anterior iliac crest as the level for measuring waist circumference, transverse and sagittal diameters and the level of throchanters for measuring hip circumference. These levels are recommended by WHO 10 and they were shown to be associated with metabolic variables by Seidell and co-workers.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantages of anthropometry are its safety, portability, and low cost. The lack of specificity of changes in the waist-to-hip ratio limits its use as a clinical tool (124)(125)(126)(127)(128)(129)(130)(131)(132). Waist circumference alone, as well as sagittal diameter, are more sensitive and specific measures than waist-to-hip ratio (120,(128)(129)(130)133).…”
Section: Recommendations For Assessment and Monitoringmentioning
confidence: 99%